Homemade citizens: The development of political interest during adolescence and young adulthood - Anja Neundorf; Kaat Smets; Gema M. García Albacete (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Despite being among the most important indicators of political participation, relatively little is known about the origins and the development of political interest over the life span. The formative years between childhood and adulthood are generally considered a crucial phase in which future electors form and strengthen political habits. The aim of this research is to better understand this important stage by examining the way in which parental socialization and lifecycle events affect the formation and growth of political interest during adolescence and young adulthood. While parental influences are expected to take place during childhood and persist over-time, life-cycle events are considered to influence development in early adulthood for those adolescents who did not grow up in a highly politicized environment. We assess these assumptions by applying latent growth curve modeling and using the German Socio-Economic Panel, which spans from 1984 - 2007. Our findings confirm strong parental socialization effects on interest levels during teenage years. While life-cycle events are not found to strongly affect the development of political interest during the formative years, the transition to adulthood is indeed a more critical period for those individuals who did not acquire high levels of interest from their family.
Keywords: 330; political interest; young adulthood; parental socialization; life-cycle events; latent growth curve analysis; panel data